Lu's basic toxicology : fundamentals, target organs, and risk assessment - Kacew, Sam (Informa Healthcare, 2013)
General Principles of ToxicologyGeneral ConsiderationsAbsorption, distribution, and excretion of ToxicantsBiotransformation of ToxicantsToxic EffectsModifying Factors of Toxic EffectsTesting Procedures for Conventional and Nontarget Organ ToxicitiesConventional Toxicity StudiesCarcinogenesisMutagenesisDevelopmental ToxicologyLactationTarget Organs and SystemsToxicology of the Immune SystemToxicology of the LiverToxicology of the KidneyToxicology of the SkinToxicology of the EyeToxicology of the Nervous SystemReproductive and Cardiovascular SystemsToxicity of Endocrine SystemToxic Substances an.